Sympathetic cooling of molecular ion motion to the ground state - R Rugango; J E Goeders; T H Dixon; J M Gray; N B Khanyile; G Shu; R J Clark; K R Brown (New Journal of Physics, 2015)
We demonstrate sympathetic sideband cooling of a ^40 CaH ^+ molecular ion co-trapped with a ^40 Ca ^+ atomic ion in a linear Paul trap. Both axial modes of the two-ion chain are simultaneously cooled to near the ground state of motion. The center of mass mode is cooled to an average quanta of harmonic motion ${{\bar{n}}_{{\rm COM}}}=0.13± 0.03$ , corresponding to a temperature of $12.47± 0.03\;μ {\rm K}$ . The breathing mode is cooled to ${{\bar{n}}_{{\rm BM}}}=0.05± 0.02$ , corresponding to a temperature of $15.36± 0.01\;μ {\rm K}$ .